Development of an Islamic values-based number theory textbook to improve conceptual understanding in mathematics education students - Fatrima Santri Syafri; Dodi Isran (Journal of Advanced Sciences and Mathematics Education, 2025)
Background : Number theory is often perceived as a difficult subject by students, particularly when taught using conventional textbooks. This challenge highlights the need for a more effective and interactive learning resource that aligns with students’ learning styles and curriculum requirements.Aim : This study aims to develop a comprehensive and curriculum-aligned number theory textbook to improve the understanding of students in the Mathematics Education Program at UIN Fatmawati Sukarno Bengkulu.Method : The research employed the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The study began with a needs analysis followed by the development of an interactive textbook. A total of 49 students participated in the study, divided into two groups: the Experimental Group (using the developed textbook) and the Control Group (using a conventional textbook). The effectiveness of the textbook was evaluated using N-Gain scores and t-tests.Results : The research found that the students in the Experimental Group, who used the newly developed textbook, demonstrated a significant improvement in understanding number theory compared to the Control Group. The Experimental Group showed a higher average N-Gain, suggesting that the developed textbook was more effective in enhancing student comprehension of number theory. The positive results indicated that the interactive and curriculum-aligned design of the textbook played a crucial role in improving the learning experience and outcomes for students.Conclusion : The findings suggest that the developed number theory textbook effectively enhances students’ comprehension and is appropriate for use as a teaching resource in the Mathematics Education Program at UIN Fatmawati Sukarno Bengkulu.